Numerical investigation of an internal solitary wave interaction with horizontal cylinders. (15th July 2020) - Ding, Weiye; Ai, Congfang; Jin, Sheng; Lin, Jinbo
Abstract: An internal solitary wave (ISW) interaction with different type horizontal cylinders are investigated. The forces induced by ISW on horizontal cylinders are presented. Distributions of the maximum dynamic pressures and flow fields around cylinders are described. Good agreements between numerical results and experimental data of forces on the isolated cylinder are achieved. For the extended cylinder, the vertical forces per unit length increase with the increase in the extended length. The horizontal forces on the extended cylinder change from increasing to decreasing after the centre-to-centre distance exceeding 3.5 times the diameter of the isolated cylinder. The peak and valley values of maximum dynamic pressures impose on the lower side of the leading edge and upper side of the trailing edge of the extended cylinder, respectively. The horizontal forces on each of the two tandem cylinders with different centre-to-centre distances are smaller than those on the isolated cylinder, indicating that the two cylinders play a role to protect each other. The comparison of forces between the two cylinders indicates that larger horizontal forces and smaller vertical forces are imposed on the rear cylinder. The maximum dynamic pressures around the rear cylinder are smaller than those around the front cylinder. Highlights: ISW interaction with horizontal cylinders of different types is investigated. Effect of the cylinder location on hydrodynamics is studied for isolated cylinders. Effect of the extended length on hydrodynamics is studied for extended cylinders. Effect of the center-to-center distance is investigated for tandem cylinders.